2004
DOI: 10.1111/j.1365-2958.2004.04377.x
|View full text |Cite
|
Sign up to set email alerts
|

BotR/A and TetR are alternative RNA polymerase sigma factors controlling the expression of the neurotoxin and associated protein genes in Clostridium botulinum type A and Clostridium tetani

Abstract: SummaryClostridium botulinum and Clostridium tetani , respectively, produce potent toxins, botulinum neurotoxin (BoNT) and tetanus neurotoxin (TeTx), which are responsible for severe diseases, botulism and tetanus. Neurotoxin synthesis is a regulated process in Clostridium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 33 publications
(75 reference statements)
2
83
0
Order By: Relevance
“…We have previously reported that BotR/A positively activates transcription of the botulinum toxin locus genes in C. botulinum A (Marvaud et al, 1998b), acting as an RNA polymerase alternative sigma factor specific for the two promoters controlling the two operons (ntnh/ A-bont/A and ha-34-ha17-ha70) of the botulinum toxin locus (Raffestin et al, 2005). BotR/A is functionally related to TetR, which controls the expression of the tent gene in C. tetani in vivo (Marvaud et al, 1998a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that BotR/A positively activates transcription of the botulinum toxin locus genes in C. botulinum A (Marvaud et al, 1998b), acting as an RNA polymerase alternative sigma factor specific for the two promoters controlling the two operons (ntnh/ A-bont/A and ha-34-ha17-ha70) of the botulinum toxin locus (Raffestin et al, 2005). BotR/A is functionally related to TetR, which controls the expression of the tent gene in C. tetani in vivo (Marvaud et al, 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of mRNA by Northern blotting and transcriptional study with purified BotR/A-RNA polymerase core enzyme has indicated that the bont/A and antp genes from C. botulinum type A1 strains such as Hall strain are transcribed in two divergent operons (ntnh/A-bont/A1 and ha34-ha17-ha70) and that bont/A1 can also be expressed separately Henderson et al, 1996;Raffestin et al, 2005). RT-PCR results showing equivalent expression levels of each gene of the botulinum toxin locus in the Hall strain are in agreement with the genetic organization in two operons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the composition of nontoxic components exhibits a certain variation according to the type of toxin, they protect the BoNTX molecules from gastric juice and intestinal digestive enzymes and facilitate the binding and adsorption of the toxins through the upper intestinal tract (4,5). Several studies have demonstrated that BoNTX genes are clustered with genes for nontoxic components and BotR, an alternative factor for the BoNTX gene cluster (4,6).…”
mentioning
confidence: 99%
“…Of the 41 nucleotide differences, 8 reside in the cntE (ha70) gene, and 29 are in the nonfunctional B3 neurotoxin-encoding gene. Importantly, we recognized that the 76-bp deletion specifically removed the Ϫ35 and Ϫ10 motifs situated upstream of cntR that had been identified as a putative CntR autoregulatory binding site (9). Of 38 other strains of proteolytic C. botulinum also possessing the ha ϩ form of the neurotoxin gene cluster (8), selected as representing a wide range of diseases caused, geographical distribution and type of neurotoxin(s) formed (3), only the type B toxin-forming strain 2345 shared the same deletion, implying that this modification is quite rare.…”
mentioning
confidence: 99%